2017
DOI: 10.1074/mcp.ra117.000057
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Mass Spectrometry Reveals Food Intake-Induced Neuropeptide Level Changes in Rat Brain: Functional Assessment of Selected Neuropeptides as Feeding Regulators

Abstract: Endogenous neuropeptides are important signaling molecules that function as regulators of food intake and body weight. Previous work has shown that neuropeptide gene expression levels in a forebrain reward site, the nucleus accumbens (NAc), were changed by feeding. To directly monitor feeding-induced changes in neuropeptide expression levels within the NAc, we employed a combination of cryostat dissection, heat stabilization, neuropeptide extraction and label-free quantitative neuropeptidomics via a liquid chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 52 publications
(61 reference statements)
2
32
0
Order By: Relevance
“…More importantly, the peptidomics is widely used to identify biological markers (31), discover new drug (32) and therapeutic targets (33). Recently, quantative peptidomics has also been conducted in endocrine studies (22, 34, 35), however, the secreted peptidomics from skeletal muscle under the insulin-resistant condition was not fully characterized.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, the peptidomics is widely used to identify biological markers (31), discover new drug (32) and therapeutic targets (33). Recently, quantative peptidomics has also been conducted in endocrine studies (22, 34, 35), however, the secreted peptidomics from skeletal muscle under the insulin-resistant condition was not fully characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with a role similar to that of NPY, transgenic animals overexpressing proSAAS are slightly overweight, and mice lacking proSAAS are leaner than wild-type littermates (Morgan et al ., 2010; Wei et al ., 2004). In addition, antibody-mediated depletion of b-LEN or PEN greatly reduced acute feeding (Wardman et al ., 2011) while injection of b-LEN into the nucleus accumbens led to elevated acute feeding (Ye et al ., 2017). Application of b-LEN to brain slices produced a rapid and reversible inhibition of synaptic glutamate release from parvocellular neurons in the hypothalamic paraventricular nucleus, a target of arcuate NPY projections (Wardman et al ., 2011).…”
Section: Orphan Neuropeptidesmentioning
confidence: 99%
“…Genetic sequence analyses predict that over 1000 potential neuropeptides may exist, with many having already been identified in CNS tissue using peptidomic approaches. In the striatum, Ye et al identified 419 m / z that correspond to potential neuropeptides and discovered that many of these peptides were regulated by behavioral manipulation [87]. Specifically, they found that proSAAS derived peptides (big LEN, PEN, and little SAAS) were decreased in mice that were unfed (hungry).…”
Section: Neuropeptides: Peptide Signals Driving Neuroplasticity Inmentioning
confidence: 99%
“…As illustrated in the studies above, traditional behavioral and molecular biology approaches can establish a functional role for neuropeptides identified using mass spectrometry. As reported by Ye et al, peptides can be site-specifically infused into brain structures to evaluate behavioral outcomes and establish a functional link with the underlying biology [87]. Likewise, peptides can be site-specifically administered by reverse-dialysis to investigate changes in levels of traditional neurotransmitters such as glutamate and GABA [93,94].…”
Section: Neuropeptides: Peptide Signals Driving Neuroplasticity Inmentioning
confidence: 99%